Burnout, personality, social support, and job satisfaction among academic staff of UiTM - Noordin, Fauziah; Othman, Rohana; Mohd Jais, Ismie Roha; Sardi, Janudin; Samsudin, Ahmad Zam Hariro (2011)
The objectives of this study are to assess the level of burnout among the academic staff of UiTM; to explore the relations of personality to the three components of burnout of the academic staff of UiTM; to examine the influence of social support on the three components of burnout of the academic staff of UiTM; to assess the effect of the three component of burnout on job satisfaction; to determine the influence of selected demographic variables on the three components of burnout, personality, social support, and job satisfaction of the academic of UiTM; and to make recommendations to the management of UiTM based on the results of the study. One thousand two hundred and ninety (1,290) sets of questionnaires were distributed to faculties, branch campuses, academic centres, and INTEC. Three hundred and eighteen completed and usable questionnaire were returned and this gave a response rate of24.65%. To provide evidence of a linear positive or negative relationship between independent and dependent variables, and to provide a measure of the strength of the relationships between variables, Pearson product-moment correlations for the variables contained in the research framework were computed. In addition, scale reliabilities of the variables were computed for the sample. This was done in order to be certain that the alpha coefficients were high. The next step in the process was to examine the inferential statistics to provide answers to the research questions. The types of inferential statistics chosen for the present study were T-tests for independent groups, and F-tests for one-way between groups ANOVA with Post-Hoc Comparison. As a test of significance, the t-test was chosen to measure significant differences between the independent and dependent variables in the study. For further analyses of the relationship between major variables and demographic variables, F-tests were computed.